Pubertal development, physical self‐perception, and motivation toward physical activity in girls. Issue 4 (3rd July 2013) - Labbrozzi, Dina; Robazza, Claudio; Bertollo, Maurizio; Bucci, Ines; Bortoli, Laura
ABSTRACT: We examined the differences in physical self‐perception and motivation toward physical activity in early‐ and mid‐adolescent girls. Body Mass Index (BMI) and pubertal status, assessed by means of the Tanner scale, were collected in 11‐year‐old ( n = 74) and 13‐year‐old girls ( n = 60). The assessment included six scales from the Physical Self‐Description Questionnaire, the Physical Activity Enjoyment Scale, and the Situational Intrinsic Motivation Scale. Age differences emerged, with older girls showing a poorer physical perception and lower scores in intrinsic motivation and enjoyment of physical activity. In the subsample of 11‐year‐olds, findings showed that more developed girls reported a poorer physical perception on the scales of body fat, global physical self‐concept, and appearance, and a lower score in the PACES positive scale. Results underscore the need to promote interventions aimed at encouraging active lifestyles among children and adolescent girls, in order to prevent overweight prior to pubertal onset.